2022
DOI: 10.18488/73.v10i3.3055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Perception Factors Influencing Collaboration Between Vocational Schools and Businesses in Practical Training

Abstract: As the global economy grows, the labor market's demand for qualified employees increases. However, the present situation is not able to meet labor market requirements; laborers are inexperienced, and their professional skills are inadequate. Collaboration between vocational schools and businesses is essential for educational activities. This study aimed to investigate the degree of perception, the contents, the forms, and the variables that influenced collaboration activities in practical training between voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This research is directed at measuring the impact of fieldwork practice and selfefficacy on vocational school students' work readiness. Nguyen et al (2022) revealed that practical learning between vocational schools and businesses is an essential prerequisite. His research findings explain that the collaboration of fieldwork practice between vocational schools and the business world is essential.…”
Section: Figure 1 Value Of Research Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This research is directed at measuring the impact of fieldwork practice and selfefficacy on vocational school students' work readiness. Nguyen et al (2022) revealed that practical learning between vocational schools and businesses is an essential prerequisite. His research findings explain that the collaboration of fieldwork practice between vocational schools and the business world is essential.…”
Section: Figure 1 Value Of Research Resultsmentioning
confidence: 99%
“…Many vocational schools strive to align their curriculum with the dynamic needs of the industry, aiming to address the skills gap and improve graduates' employability (Nguyen et al, 2022), such as practice-based education models that combine school and business or industry (Ryan, 2001). Collaboration between school and industry represents a critical mass in the German education system as it forms the backbone of the dual training system (Ohlemann & Driesel-Lange, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a few studies have been carried out in Vietnam to assess the importance of vocational training coordination activities for the labor market and the career performance of students. According to research by Van Nguyen, Cao, and Nguyen (2022), students, teachers and technical staff at vocational schools and businesses were aware of the significance of collaborative teaching practices.…”
Section: Introductionmentioning
confidence: 99%